Genetic diversity in apple tree cultivars established in the Sierra de Arteaga, Coahuila, Mexico - Escobar Saucedo, Mayra Alejandra; Aguilar, Cristobal; Vázquez Ramos, Antonio; Reyes Valdés, Manuel Humberto; Rodríguez Herrera, Raúl (Ecosistemas y Recursos Agropecuarios, 2018)
Apple production in the Sierra de Arteaga, Coahuila is mainly based on the Golden Delicious cultivar. Production based on only a few cultivars represents a genetic risk, because if they are susceptible to a pest, disease or climate change much of this production would be lost if one or more of these conditions occurred. Foreseeing this situation, farmers have introduced different commercial apple cultivars, but there is little information about the genetic diversity among them. Therefore, the aim of this study was to estimate the rates of intraspecic genetic diversity of 12 different apple cultivars using inter-simple sequence repeat (ISSR) molecular markers. Employing nine ISSR primers, it was possible to identify 124 DNA bands, of which 63% were polymorphic, with genetic diversity of 0.24. Results suggest that these cultivars are adapted to the region’s climate and can be utilized to increase the overall plantation area, in order not to depend on a single cultivar.